Pyoderma gangrenosum and anticardiolipin antibody - de Godoy Jose Maria; Batigalia Fernando; Braile Domingo (Wolters Kluwer Medknow Publications, 2006)
Pyoderma gangrenosum (PG) is a rare ulceronecrotic inflammatory cutaneous disorder and is frequently associated with systemic diseases. The authors report a 22-year-old male patient with pyoderma gangrenosum, thrombosis of both popliteal arteries, ischemic stroke and seropositivity for anticardiolipin antibody. Despite intravenous treatment with antibiotics, corticosteroid and heparin, pyoderma gangrenosum caused necrosis of his right lower limb which resulted in amputation. It was concluded that the anticardiolipin antibody may have contributed to the gravity of this case.